2016
DOI: 10.1007/s10570-016-0987-x
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and rheology of cellulose nanofibrils derived from mixtures of pulp fibres and papermaking fines

Abstract: The rheological behaviour of homogenised fibres originally having different lengths was evaluated. For this purpose, mixtures of pulp fibres and fines were fibrillated mechanically without pretreatment and characterised with regard to morphology and viscosity. It was found that, for all samples, a similar number of homogenisation passes was needed to reach a viscosity plateau. However, the value of the final viscosity differed significantly: homogenised suspensions derived from fines achieved only about 60 % o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 25 publications
2
19
0
1
Order By: Relevance
“…3) showed an increase in storage (G 0 ) and loss moduli (G 00 ) between 5 and 10 passes but both the moduli stabilized at certain level between 10 and 15 passes. This confirms the results obtained by Grüneberger et al (2014) and Colson et al (2016) who compared viscosities of mechanically fibrillated samples and found a viscosity plateau after a certain number of mechanical fibrillation steps. Grüneberger et al (2014) reported that the viscosity levelled off after 5-8 passes and Colson et al (2016) reported a levelling off after 10-14 passes.…”
Section: Rheological Propertiessupporting
confidence: 92%
“…3) showed an increase in storage (G 0 ) and loss moduli (G 00 ) between 5 and 10 passes but both the moduli stabilized at certain level between 10 and 15 passes. This confirms the results obtained by Grüneberger et al (2014) and Colson et al (2016) who compared viscosities of mechanically fibrillated samples and found a viscosity plateau after a certain number of mechanical fibrillation steps. Grüneberger et al (2014) reported that the viscosity levelled off after 5-8 passes and Colson et al (2016) reported a levelling off after 10-14 passes.…”
Section: Rheological Propertiessupporting
confidence: 92%
“…The rheological characteristics of various CMNF suspensions has become a widely discussed topic. Although knowledge on rheological behavior is naturally important in the use of CMNFs as a rheology modifier (Dimic-Misic et al 2013;Shao et al 2015;Li et al 2015) and stabilizer (Andresen and Stenius 2007;Winuprasith and Suphantharika 2013), such information is also needed for CMNF production (Delisée et al 2010;Pääkkönen et al 2016;Colson et al 2016) and for other CMNF-related processes (Saarikoski et al 2015;Shao et al 2015;Hoeng et al 2017;Kumar et al 2017). A recent thorough review of the rheology of CMNF suspensions can be found in (Hubbe et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The rheological characteristics of various MNFC suspensions have become a widely discussed topic. Although knowledge of the rheological behavior is naturally important in the use of MNFC as a rheology modifier (Dimic-Misic et al 2013a;Shao et al 2015;Li et al 2015) and stabilizer (Andresen and Stenius 2007;Winuprasith and Suphantharika 2013), such information is also needed for MNFC production (Pääkkönen et al 2016;Delisée et al 2010;Colson et al 2016) and for other MNFC-related processes (Saarikoski et al 2015;Hoeng et al 2017;Shao et al 2015;Kumar et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…There are many variables that can influence the rheological behavior of MNFC suspensions. These include consistency van de Ven 2014, 2015;Charani et al 2013), size distribution and morphology (Colson et al 2016;Zhang et al 2012;Saarikoski et al 2012;Agoda-Tandjawa et al 2010;Dimic-Misic et al 2013b;Gourlay et al 2018), composition (Pääkkönen et al 2016), modifications to the cellulose surface (Samyn and Taheri 2016;Lasseuguette et al 2008), ionic strength (Lowys et al 2001;Saarikoski et al 2012), and effects of various polymers (Karppinen et al 2011;Agoda-Tandjawa et al 2012;Naderi and Lindström 2014). Recent reviews on MNFC rheology can be found in Colson et al (2016), Nechyporchuk et al (2016) and Hubbe et al (2017).…”
Section: Introductionmentioning
confidence: 99%